Religious Character Formation in Students with Intellectual Disabilities through Spiritual Counseling: A Field Evaluation Integrated with Bibliometric Analysis - Maulana, Muhammad Fikri; Khilmiyah, Akif (Universitas PGRI Yogyakarta, 2026)
The development of religious character among children with intellectual disabilities remains a neglected field in inclusive education, despite its critical role in fostering moral awareness and social adaptation. This study aims to evaluate methods for internalizing religious character values through spiritual counseling services at Extraordinary School of Pembina Yogyakarta, while mapping global research trends in this domain. Using a convergent parallel mixed-methods design, qualitative data were collected through interviews, observations, and document analysis, complemented by a bibliometric analysis of 247 Scopus-indexed publications (2014–2024) using VOSviewer. The results reveal four effective strategies: spiritual individual counseling, group guidance via visual and audio media, ritual habituation, and counselor–parent collaboration. Bibliometric findings identified five major clusters: character education, inclusive learning, disability counseling, religious values, and adaptive pedagogy. This study enriches Lickona’s and Bandura’s frameworks by contextualizing religious character education for children with intellectual disabilities and underscores the need for standardized counseling modules and continuous counselor training. Keywords: internalization of religious values, intellectual disability, guidance and counseling, character education